2022
DOI: 10.1002/pon.5929
|View full text |Cite
|
Sign up to set email alerts
|

Scoping the psychological support practices of Australian health professionals working with people with primary brain tumor and their families

Abstract: Objectives This study aimed to scope the psychological support practices of Australian health professionals providing supportive care to adults with primary brain tumor. Method Health professionals from multidisciplinary organizations and cancer support services completed an online survey focused on psychological support for people with brain tumor (PwBT) and family members, and perceived barriers or gaps in support provision. Results 107 professionals, mainly from psychology (45%), nursing (20%), and social w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…Our team has conducted studies to determine the unmet needs of patients diagnosed with high-grade glioma [ 48 ] and their carers [ 49 , 50 ] and also developed an intervention to assist in carer preparedness following diagnosis [ 51 , 52 ]. Additionally, work is being conducted in Australia to understand current support services available to patients [ 53 , 54 ] and to develop and test psychosocial interventions that provide additional support to patients [ 55 ]. Internationally several studies have been conducted on patient and carer needs and interventions to support them [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our team has conducted studies to determine the unmet needs of patients diagnosed with high-grade glioma [ 48 ] and their carers [ 49 , 50 ] and also developed an intervention to assist in carer preparedness following diagnosis [ 51 , 52 ]. Additionally, work is being conducted in Australia to understand current support services available to patients [ 53 , 54 ] and to develop and test psychosocial interventions that provide additional support to patients [ 55 ]. Internationally several studies have been conducted on patient and carer needs and interventions to support them [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to recruit a minimum of 20 HPs from different disciplines, clinical settings, states, and territories across Australia. Participants were recruited from a national survey of 107 HPs, 26 which invited them to indicate interest in being interviewed. After initial recruitment of 14 HPs, purposeful and snowballing sampling was used to recruit a further seven participants to increase representation of different disciplines and clinical settings.…”
Section: Methodsmentioning
confidence: 99%
“…Research on psychosocial support needs of PwBT and their families highlights the need for flexible and timely access to support based on individual needs from diagnosis into long‐term survivorship and end‐of‐life care 20,24 . However, a recent survey 26 of 107 Australian HPs identified variability in provision of psychosocial support according to HP discipline, setting and illness phase. Psychosocial support was more commonly provided to PwBT than family members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 This is echoed by health professionals, who identified system-level barriers including limited resources, funds, and availability of staff with brain-tumor specific training. 6 Several recent systematic reviews have collated the current evidence-base for supportive interventions for neurooncology caregivers-including those who are bereaved. [7][8][9] A Cochrane systematic review from Boele et al identified eight small-scale trials (range N = 13-56).…”
mentioning
confidence: 99%